2012
DOI: 10.1177/1934578x1200700401
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Absolute Stereochemistry of Limonene and α-Santalol by Raman Optical Activity Spectroscopy

Abstract: Determining the absolute stereochemistry of organic compounds in solution remains a challenge. We investigated the use of Raman optical activity (ROA) spectroscopy to address this problem. The absolute configurations of (+)-(R)-and (-)-(S)-limonene were determined by ROA spectroscopy, which can be applied to smaller amounts of sample as compared with vibrational circular dichroism (VCD) spectroscopy. This ROA method was also applied to (+)-(E)--santalol and shown to be successful in the determination of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…These works also reveal that IR, Raman, and VCD are helpful complementary techniques for characterizing exible systems. 111 The lupane triterpenoid epoxylupenone (61), prepared from lupeol, had its 20S absolute conguration determined by comparison of observed and calculated (B3LYP/DGDZVP) spectra. Compound 43 was assigned as 1R and the authors indicated B3LYP/DGDZVP calculations as providing a superior balance between computational cost and VCD spectral accuracy.…”
Section: Terpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…These works also reveal that IR, Raman, and VCD are helpful complementary techniques for characterizing exible systems. 111 The lupane triterpenoid epoxylupenone (61), prepared from lupeol, had its 20S absolute conguration determined by comparison of observed and calculated (B3LYP/DGDZVP) spectra. Compound 43 was assigned as 1R and the authors indicated B3LYP/DGDZVP calculations as providing a superior balance between computational cost and VCD spectral accuracy.…”
Section: Terpenesmentioning
confidence: 99%
“…110 The absolute conguration of (+)-(R)-5 and its antipode, as well as that of (+)-(E)-a-santalol (60), were determined using ROA spectrosocopy. 111 The lupane triterpenoid epoxylupenone (61), prepared from lupeol, had its 20S absolute conguration determined by comparison of observed and calculated (B3LYP/DGDZVP) spectra. 112 Once again, VCD analysis was able to distinguish between two possible epimers of a natural product.…”
Section: Terpenesmentioning
confidence: 99%
“…132 Raman optical activity spectroscopy has been used in the determination of the absolute stereochemistry of (+)-(E)-a-santalol, showing that this technique is a useful tool for these purposes. 133 A synthesis of (À)-b-santalol has been described. 134 The preparation of fumagillol derivatives, useful for the treatment and prevention of bone tumours, has been patented.…”
Section: Bisabolane and Sesquisabinanementioning
confidence: 99%
“…ROA has been predominantly used to characterize the structure of macromolecules in aqueous solution with many examples reported for peptides, proteins, , nucleic acids, carbohydrates, and even viral coat proteins . However, only a few examples can be found for its application to natural product chemistry. Herein we present the first report of the use of experimental and quantum chemical calculated ROA for determining the absolute configuration of diterpenoids.…”
mentioning
confidence: 99%